2012
DOI: 10.1152/ajpregu.00336.2011
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise increases NF-κB activity in human skeletal muscle

Abstract: Intense resistance exercise causes a significant inflammatory response. NF-κB has been identified as a prospective key transcription factor mediating the postexercise inflammatory response. The purpose of this study was to determine whether a single bout of intense resistance exercise regulates NF-κB signaling in human skeletal muscle. Muscle biopsy samples were obtained from the vastus lateralis of five recreationally active, but not strength-trained, males (21.9 ± 1.3 yr) prior to, and at 2 and 4 h following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 46 publications
12
61
0
Order By: Relevance
“…In agreement with our findings, prior studies have demonstrated that the mRNA expression of CX3CL1 tends to decrease slightly over time in resting/nonexercising skeletal muscle (6,70). Intriguingly, however, the expression of CCL2 has been reported to increase, albeit not significantly, in resting muscle 2-4 h following a baseline biopsy (6,70,78). These changes in the expression of key myokines illustrate the critical importance of incorporating a control group in long experiments to account for time-dependent variations in skeletal muscle gene expression in humans.…”
Section: Skeletal Muscle Angiogenic Signalingsupporting
confidence: 92%
“…In agreement with our findings, prior studies have demonstrated that the mRNA expression of CX3CL1 tends to decrease slightly over time in resting/nonexercising skeletal muscle (6,70). Intriguingly, however, the expression of CCL2 has been reported to increase, albeit not significantly, in resting muscle 2-4 h following a baseline biopsy (6,70,78). These changes in the expression of key myokines illustrate the critical importance of incorporating a control group in long experiments to account for time-dependent variations in skeletal muscle gene expression in humans.…”
Section: Skeletal Muscle Angiogenic Signalingsupporting
confidence: 92%
“…Exercises were performed sequentially in a circuit manner with participants resting for 1 min between each exercise and 3 min between each set. This same exercise protocol has been previously used by our research group to induce local proinflammatory cytokine expression and associated NF-B signaling in human skeletal muscle (106). Following completion of the exercise bout, subjects rested supine throughout a 3-h recovery period, during which postexercise blood samples were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Through the activation of satellite cell proliferation, NO is important in damage repair/remodeling in the skeletal muscle, which might be important in delayed muscle soreness (315). B Redox sensor, regulates genes related with inflammation, cell growth, stress responses, including oxidative stress, and apoptosis E Activation of NF-jB binding to DNA in rat skeletal muscle in response to acute treadmill running (111,139,142,162) NF-jB activation in human peripheral blood lymphocytes in response to acute spring and endurance exercise (76,420) Acute treadmill exercise activates NF-jB in an intensity-dependent manner in human peripheral blood lymphocytes (182) Acute eccentric exercise induces and submaximal eccentric training decreases NF-kB activation in PBMC (101,165) Acute intensive resistance exercise increases NF-jB activity in human skeletal muscle (418) Acute fatiguing resistance exercise decreases NF-jB binding to DNA in skeletal muscle from healthy humans and mice (87) NF-jB activation in response to moderate-intensity cycle exercise in muscle from nondiabetic subjects, but not in type II diabetics (392) Increased basal NF-jB activity in muscle from insulin-resistant and type II diabetic subjects, and in diabetic rat (197,392) NF-jB activation for DNA binding by isometric contraction in muscle of adult, but not old mice (416) Muscle unloading increases NF-jB activity in mice (87,150) NF-jB -/ -mice is resistant to unloading-induced muscle atrophy (149) Training increases basal levels, but blunts isometric contraction-induced NF-jB activation in skeletal muscle of mice (53) Treadmill training increases nuclear levels of NF-jB in skeletal muscle of adult and old rats (105) T Activator protein-1 (AP-1)…”
Section: Exercise-induced Inflammation and Rosmentioning
confidence: 99%